Mythical association of male body in Baahubali series (Journal of Innovation in Academia, 2025)
This study entitled as “Mythical Association of Male Body in Baahubali Series” explores how S.S. Rajamauli destabilizes the cinematic convention of the constructed female body in consideration of the male gaze in the Bollywood film industry. It investigates the entertainment industry’s presentation of the male body for both the male and female gaze in Baahubali Series. The research paper examines the texts from the perspectives of Body Studies and the body myth from the Eastern epic traditions, including Mahabharata, Ramayana and Hindu hymns. Similarly, the body of Baahubali rehearses Bhima and Krishna, the body of Bhalla Deva with Duryodhana and the body of Bajjala Deva with Dhritarastra. Since the representation of the body in Bollywood movies has barely been explored, this study can be significant source for the researchers of myth, movie and masculinity in the future.